Conventions of Malaysian Grocery Store Service Encounters - Soong, Gze Peng; Ting, Su Hie (Hermes (Denmark), 2015)
The study aims to describe the conventions of the Malaysian model of service encounters and contrast them to the model proposed by Halliday/Hasan (1985) by focusing on interactions between Chinese service providers and customers from different ethnic groups in a grocery store. A total of 120 service encounters (60 with Chinese customers, 60 with non-Chinese customers) were observed and audio-taped. Analysis of the service encounters showed that Sale Request, Sale, Purchase and Goods Handover are obligatory stages in the shop, but a low frequency of Greeting, Sale Initiation and Finis was found. The infrequent use of politeness features resembling interpersonal interactions indicates a taskfocussed interaction between the service provider and customer. The results also indicate some in/outgroup differences in the Chinese service providers’ interaction with their Chinese and non-Chinese customers. The service providers were more likely to engage in Greeting and Finis with Chinese customers, and Sale Initiation with non-Chinese customers, indicating a clearer service provider-customer role and a stronger task-focus in interactions with outgroup members. The stages that are more likely to be enacted non-linguistically are Sale Request, Purchase and Goods Handover. In the grocery store, customers often brought goods they wanted to purchase to the counter, making verbalisation of Sale Request unnecessary. The non-Chinese customers were more inclined to make non-verbal Sale Requests than Chinese customers, whereas service encounters with Chinese customers had relatively more frequent non-verbalised Sale Compliance and Sale stages. The possible relevance of in/outgroup relationship on non-verbal communication in service encounters needs further investigation.